2015
DOI: 10.1016/j.biopsych.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Gq-DREADD Selectively Initiates Glial Glutamate Release and Inhibits Cue-induced Cocaine Seeking

Abstract: Background Glial cells of the central nervous system directly influence neuronal activity by releasing neuroactive small molecules, including glutamate. Long-lasting cocaine-induced reductions in extracellular glutamate in the nucleus accumbens core (NAcore) affect synaptic plasticity responsible for relapse vulnerability. Methods We transduced NAcore astrocytes with an AAV viral vector expressing hM3Dq (Gq) DREADD under control of the glial fibrillary acidic protein (GFAP) promoter in 62 male Sprague Dawley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
147
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(171 citation statements)
references
References 63 publications
12
147
0
Order By: Relevance
“…Electrochemical recordings demonstrated that astroglial G q -DREADD activation results in a reliable increase of glutamate release in the NAc core, and this manipulation is associated with an inhibition of cueinduced cocaine seeking (Scofield et al, 2015). Subsequent experiments suggested that the protective effect of astroglial stimulation was related to synaptic signaling for metabotropic glutamate receptors mGluR2/3 (Scofield et al, 2015). These data suggest that astrocytes can directly influence drug-seeking behavior for cocaine, and the methodologies employed emphasize the opportunities for glial cell-type-specific manipulations in the context of addiction.…”
Section: Psychostimulants Glia and Neuroimmune Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrochemical recordings demonstrated that astroglial G q -DREADD activation results in a reliable increase of glutamate release in the NAc core, and this manipulation is associated with an inhibition of cueinduced cocaine seeking (Scofield et al, 2015). Subsequent experiments suggested that the protective effect of astroglial stimulation was related to synaptic signaling for metabotropic glutamate receptors mGluR2/3 (Scofield et al, 2015). These data suggest that astrocytes can directly influence drug-seeking behavior for cocaine, and the methodologies employed emphasize the opportunities for glial cell-type-specific manipulations in the context of addiction.…”
Section: Psychostimulants Glia and Neuroimmune Signalingmentioning
confidence: 99%
“…To manipulate intracellular calcium signaling in a discrete population of astrocytes, the authors utilized viral mediated transfection to express the designer receptor exclusively activated by a designer drug (DREADD) hM3D (a designer G q -protein coupled receptor) under the control of the GFAP promoter (Scofield et al, 2015). This method allows for pharmacological control of astrocyte intracellular signaling.…”
Section: Psychostimulants Glia and Neuroimmune Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological analyses reveal that cocaine-and heroin-induced loss of LTD and LTP induced in the NAcore after in vivo electrical stimulation of the PFC is reversed by daily NAC treatment Shen and Kalivas, 2013). Interestingly, the ability Scofield et al, 2015 xCT, the catalytic subunit of the cystine-glutamate exchanger.…”
Section: F Glial Glutamate Release and Uptakementioning
confidence: 99%
“…Others have demonstrated that CNO alone has no effect on reinstatement behaviors or psychostimulant self-administration (Ferguson et al 2011;Mahler et al 2014;Scofield et al 2015;Augur et al 2016;Kerstetter et al 2016). However, Gomez et al implicate clozapine as the specific ligand to DREADDs and its back metabolism from CNO to engage DREADD-mediated changes in cell function (2017).…”
Section: Cno Administration Does Not Induce Reinstatement Behavior Inmentioning
confidence: 99%